2018
DOI: 10.2175/106143017x15054988926604
|View full text |Cite
|
Sign up to set email alerts
|

Zr‐Metal Organic Framework and Derivatives for Adsorptive and Photocatalytic Removal of Acid Dyes

Abstract: To investigate effects of modification of MOFs on removal of acid dyes via adsorption and photodegradation, zirconium-based MOF, UiO-66, and its derivatives were synthesized. UiO-66 derivatives were prepared by using amine (NH2)-containing ligand and incorporating carbon nanotubes (CNTs) and reduced graphene oxide (RGO). During the synthesis UiO-66-NH2, UiO-66-CNT and UiO-66-RGO, were obtained, respectively. While UiO-66-NH2 showed the enhanced adsorption capacity for acid dyes owing to the electrostatic attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 63 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…[22] Therefore, it is indispensable to remove pollutants (such as XO and TC) from aqueous environments. Also, previous studies [20][21]23] have reported the cases of photocatalytic removal of antibiotics and acid dyes over MOFs, which indicated MOFs have potential adsorption performance.…”
Section: Introductionmentioning
confidence: 93%
“…[22] Therefore, it is indispensable to remove pollutants (such as XO and TC) from aqueous environments. Also, previous studies [20][21]23] have reported the cases of photocatalytic removal of antibiotics and acid dyes over MOFs, which indicated MOFs have potential adsorption performance.…”
Section: Introductionmentioning
confidence: 93%
“…Lin et al [177] synthesized UiO-66, NH2-UiO-66, GO/UiO-66, and CNT/UiO-66 to investigate the adsorption of two acid dyes including AO7 and AY17 from the aquatic environment. For AO7 adsorption, the maximum capacity obtained was 42.6, 55, 80.6, and 66.198 mg/g for UiO-66, NH2-UiO-66, CNT/UiO-66, and GO/UiO-66, respectively.…”
Section: Go-and Cnt-mof Nanocomposites In Dye Removalmentioning
confidence: 99%
“…At the GO content of 25% (w/w), GO sheets would cover the MOF structure and hinder dye adsorption on the active surface sites of MOF, resulting in a drop in the adsorption capacity. Lin et al [177] synthesized UiO-66, NH 2 -UiO-66, GO/UiO-66, and CNT/UiO-66 to investigate the adsorption of two acid dyes including AO7 and AY17 from the aquatic environment. For AO7 adsorption, the maximum capacity obtained was 42.6, 55, 80.6, and 66.198 mg/g for UiO-66, NH 2 -UiO-66, CNT/UiO-66, and GO/UiO-66, respectively.…”
Section: Go-and Cnt-mof Nanocomposites In Dye Removalmentioning
confidence: 99%
“…Zn based metal-organic frameworks have been reported to adsorb amodiaquine, whereas carbon nanotubes, graphene and its derivatives were also utilized for adsorption of diclofenac, carbamazepine, and ciprofloxacin [164].…”
Section: Absorption Onto the Sludgementioning
confidence: 99%